Nanoscale C‐Rich SixC1−x Bus/Ring Waveguide Based Cross‐Wavelength Data Converter. Issue 2 (15th January 2019) - Syu, Shih‐Chang; Cheng, Chih‐Hsien; Wang, Huai‐Yung; Chi, Yu‐Chieh; Lin, Gong‐Ru
Abstract: The carbon‐rich silicon carbide (C‐rich Si x C1− x ) micro‐ring channel waveguide with asymmetric core aspect is demonstrated for all‐optical cross‐wavelength pulsed return‐to‐zero on‐off keying (PRZ‐OOK) data conversion. Enhanced nonlinear optical Kerr switching enables 12‐Gbit per second data processing with optimized modulation depth. The inverse tapered waveguide at end‐face further enlarges the edge‐coupling efficiency, and the asymmetric channel waveguide distinguishes the polarization modes. To prevent data shape distortion, the bus/ring gap spacing is adjusted to control the quality factor (Q‐factor) of the micro‐ring. Designing the waveguide cross section at 500 × 350 nm 2 provides the C‐rich Si x C1− x channel waveguide to induce strong transverse electric mode (TE‐mode) confinement with a large Kerr nonlinearity of 2.44 × 10 −12 cm 2 W −1 . Owing to the trade‐off between the Q‐factor and the on/off extinction ratio, the optimized bus/ring gap spacing of 1400 nm is selected to provide a coupling ratio at 5–6% for compromising the modulation depth and the switching throughput. Such a C‐rich Si x C1− x micro‐ring with asymmetric channel waveguide greatly enhances the cross‐wavelength data conversion efficiency to favor its on‐chip all‐optical data processing applications for future optoelectronic interconnect circuits. Abstract : A carbon‐rich silicon carbide (C‐rich Si x C1− x ) micro‐ring waveguide with smallest core aspect asymmetry is demonstrated for all‐optical cross‐wavelength conversion up to 12 Gbit per second, performed by enhancing the nonlinear Kerr switching. An optimized asymmetry of C‐rich Si x C1− x micro‐ring waveguide enhances the cross‐wavelength conversion efficiency to favor the onchip all‐optical data processing in future optoelectronic inter‐connect circuits.